Desarrollo de un método analítico para compuestos anabólicos utilizando GC / PTV /EI / MS - Velázquez Chong, Laura Renné; Rodríguez Valdés, Osvaldo Nicolás; Soto Alvarado, Sonia del Carmen; Rodríguez Ventura, Guillermo; Escoboza García, Isabel; Sánchez López, Eduardo (Acta Universitaria, 2009)
The use of a programmable temperature vaporizing injector (PTV), unlike the classic isothermal injectors in coupled gas chromatography/mass spectrometry systems (GC/MS), has opened new analytical pathways in the determination of different families of anabolically active compounds used as growth promoters in cattle fattening. With the analytical combination of GC/PTV/EI/MS a reliable method of measurement has been created that allows the detection and structural identification of different families of natural and synthetic anabolic compounds in animal tissues, at ultratrace levels with quantification limits up to 0,25 Î¼g/kg. This new method represents a valuable alternative in the analysis of the anabolic compounds Dietilestilbestrol, Zeranol and Taleranol, monitored by the Official Mexican Norm NOM-034-ZOO-1996, because it reduces the steps required in the treatment of the sample, and in the PTV injector an additional cleaning of the reaction matrix is done, and the derivatization reactions of these compounds are done under controlled pressure and temperature with a recovery in the bovine muscle of between 70 and 120%.